2012
DOI: 10.5267/j.msl.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social capital and employee participation in Gorgan medical science university

Abstract: In this article, we investigate the relationship between social capital and employee participation in Gurgan Medical Science University. The results of our study indicate that there is an indirect relationship between employee participation networks and employee participation, an indirect relationship between trust and closeness with employee participation and there is an indirect relationship between employee closeness and employee participation. Our investigation shows that there is a relationship between tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…Also, according to the findings, there was a direct association between social capital and job performance; so that the higher the social capital, the higher would be the job performance of faculty members. This finding is consistent with the findings of several studies (11,(14)(15)(16). The Health Scope.…”
Section: Discussionsupporting
confidence: 93%
“…Also, according to the findings, there was a direct association between social capital and job performance; so that the higher the social capital, the higher would be the job performance of faculty members. This finding is consistent with the findings of several studies (11,(14)(15)(16). The Health Scope.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, our research confirmed a direct and significant relationship between social capital and job performance; so that strengthening social capital in the workplace increased job performance among university faculty members. This result was also confirmed by findings of several studies [19,[25][26][27].…”
Section: Discussionsupporting
confidence: 91%
“…Social capital plays essential role in education systems as will. Alinajafi et al (2012), for example, investigated the relationship between social capital and employee participation in Gorgan medical science university and reported that social capital influences positively on building intangible assets within industry. Azma et al (2012) performed another empirical investigation and considered the application of information technology and its relationship with organizational intelligence.…”
Section: Introductionmentioning
confidence: 99%